Improving The QOS In MANET Using Dynamic Efficient Power Consumption Based Congestion Control Scheme (International Journal of Engineering and Computer Science, 2017)
: The Mobile Ad hoc Networks are considered as a new paradigm of infrastructure-less mobile wireless communication systems. Routing in MANETs is considered as a challenging task due to the unpredictable changes in the network topology, Nodes can dynamically join and leave the network without any warning and All nodes in network are energy dependent and efficient energy utilization is one of the important criteria in MANET. In this research work, propose the Dynamic Efficient Power Consumption Congestion Control Scheme (DEPCCCS) for congestion control and improving the quality of service in mobile network. The dynamic behavior of network connection is not maintained for long time. In a mobile network nodes are not aware about their energy status, some situation routing packets are consumes more energy. In this paper, the  DEPCCCS is incorporated in the routing protocol to reduces that possibility of destination finding by maintain the record of location of each node in network respect to wireless base station is used. The central base station stores locations of the mobile nodes in a position table. The proposed protocol dynamically calculates every nodes energy status and their current location and speed for the minimum energy consumption for mobile nodes. And also the proposed scheme presents congestion control and power consumption. By simulation results, shown that our proposed technique attains better delivery ratio and throughput with less delay and energy consumption when compared with the  existing technique